Acylation stimulating protein is higher in Inuit from Nunavik compared to a southern Quebec population - Smith, Jessica; Cianflone, Katherine M.; Dewailly, Éric; Chateau-Degat, Marie-Ludivine; Vohl, Marie-Claude; Julien, Pierre (International Association of Circumpolar Health Publishers, 2009)
Objectives. The Inuit of Nunavik in northern Quebec have a lower risk for ischemic heart disease (IHD) compared to Caucasian populations. Acylation stimulating protein (ASP), which is involved in the storage of dietary fat, may play a role. The objective of the study was to determine plasma concentration of ASP in an Inuit and a southern Quebec Caucasian population. Study design. This is a cross-sectional study evaluating the relationship between ASP and dietary factors, such as retinol, whose intake is higher in the Inuit. As well, concentrations of ASP were evaluated in relationship to components of the metabolic syndrome. Methods. Medical history was collected via a questionnaire and anthropometric measurements and blood samples were collected. Results. ASP was significantly higher in both the Inuit men and women compared to Caucasian men (66.1±4.1 nM vs 27.5±2.5 nM, p<0.0001) and women (71.8±3.8 nM vs 29.4±1.3 nM, p<0.0001). In addition, ASP significantly correlated with total retinol (r=0.17, p=0.02) and free retinol (r=0.15, p=0.04) in Inuit men but not with other distinctive dietary markers such as omega3 fatty acids. Conclusions. Inuit men and women have higher ASP which was unrelated to the number of risk factors for IHD that were present.